2000
DOI: 10.1021/ac000661e
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Electrophoretic Migration and Separation of Liposomes by Capillary Zone Electrophoresis in Electrolyte Solutions of Various Ionic Strengths

Abstract: The size-dependent electrophoretic migration and separation of liposomes was demonstrated and studied in capillary zone electrophoresis (CZE). The liposomes were extruded and nonextruded preparations consisting of phosphatidylcholine/phosphatidylglycerol/cholesterol in various ratios and ranging from 125 to 488 nm in mean diameter. When liposomes of identical surface charge density were subjected to CZE in Tris-HCl (pH 8) buffers of various ionic strengths (0.001-0.027), they migrated in order of their size. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
71
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 21 publications
4
71
0
Order By: Relevance
“…Although flow cytometry was historically used first to detect individual organelles [9,10], CE has the additional analytical advantage of being able to separate organelles based on their electrophoretic mobilities [11][12][13][14]. In general, the electrophoretic mobility of a particle stems from its size [12,14,19] and surface characteristics [13,19], which makes CE useful for comparing the size or surface characteristics of individually detected biological species, such as proteins [15], mitochondria [8,16], nuclei [17], and acidic organelles [18]. The size and surface characteristics of these particles may be highly heterogeneous, making it extremely important to analyze samples with a sufficient number of individual species so that an accurate statistical description is observed.…”
Section: Introductionmentioning
confidence: 99%
“…Although flow cytometry was historically used first to detect individual organelles [9,10], CE has the additional analytical advantage of being able to separate organelles based on their electrophoretic mobilities [11][12][13][14]. In general, the electrophoretic mobility of a particle stems from its size [12,14,19] and surface characteristics [13,19], which makes CE useful for comparing the size or surface characteristics of individually detected biological species, such as proteins [15], mitochondria [8,16], nuclei [17], and acidic organelles [18]. The size and surface characteristics of these particles may be highly heterogeneous, making it extremely important to analyze samples with a sufficient number of individual species so that an accurate statistical description is observed.…”
Section: Introductionmentioning
confidence: 99%
“…Among the techniques used for the separation of colloids and biologic macromolecules, CE has been established as a reliable and widely useful analytical technique with high resolution, high efficiency, and high automation capability [4,5]. A broad range of colloids including polystyrene lattices [6][7][8], silica sols [9], semiconductor clusters [10], virus and bacterial particles [11,12], and liposomes [13,14] have been separated by CE. The size distribution of various colloid particles, their surface charge density, and relaxation effect under electric field can be effectively evaluated using CE.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, they can be analyzed by CE, and they proved useful as anionic pseudostationary phases in EKC ( ; for recent reviews see [23,24]. It was found that, besides the pH, the kind of the electrolytes [6,25] and its ionic strength [5,18], and the preparation procedure of the vesicles influences the electrophoretic properties of the particles [23,26]. If their electrophoretic mobility is affected upon attachment of ligands, this change can be used to assess, or even quantify, the interaction in a form of ACE.…”
Section: Introductionmentioning
confidence: 99%
“…The number of lipid molecules in the bilayer (with a mass of 5610 216 g per vesicle, see above) is about 3610 5 (taking 1000 Da as an approximate molecular weight of the lipid). Taking into account that the DOGS-NTA contributes 5% to the total lipid in the bilayer, it can be estimated that each vesicle contains roughly 15 000 DOGS-NTA molecules and consequently the same number of Niions.…”
mentioning
confidence: 99%